2013
DOI: 10.1155/2013/283490
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality among Female Hospital Staff Nurses

Abstract: Purpose. To investigate sleep quality of hospital staff nurses, both by subjective questionnaire and objective measures. Methods. Female staff nurses at a regional teaching hospital in Northern Taiwan were recruited. The Chinese version of the pittsburgh sleep quality index (C-PSQI) was used to assess subjective sleep quality, and an electrocardiogram-based cardiopulmonary coupling (CPC) technique was used to analyze objective sleep stability. Work stress was assessed using questionnaire on medical worker's st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
67
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 18 publications
19
67
2
3
Order By: Relevance
“…59%-76%가 수면의 질 저하를 경험하는 것으로 나타났으며 (Chien et al, 2013;Hsieh et al, 2011), 우리나라의 경우 상당 수의 교대근무 간호사들이 수면 만족도의 저하나 주간 기능 장애 등을 경험하고 있는 것으로 확인되었다 (Han et al, 2011). 간호사의 수면장애는 피로나 불안 및 우울 등 신체적, 정신적 건강문제를 유발할 뿐만 아니라, 간호 현장에서 업무 실수나 사고 등 직‧간접적인 업무 오류를 발생시킬 수 있다 (Chan, 2009;Dorrian et al, 2008).…”
Section: 수면장애는 교대근무를 하는 간호사들에게 흔히 발생하는 문제로 알려져 있다 외국의 경우 교대근무 간호사들의unclassified
“…59%-76%가 수면의 질 저하를 경험하는 것으로 나타났으며 (Chien et al, 2013;Hsieh et al, 2011), 우리나라의 경우 상당 수의 교대근무 간호사들이 수면 만족도의 저하나 주간 기능 장애 등을 경험하고 있는 것으로 확인되었다 (Han et al, 2011). 간호사의 수면장애는 피로나 불안 및 우울 등 신체적, 정신적 건강문제를 유발할 뿐만 아니라, 간호 현장에서 업무 실수나 사고 등 직‧간접적인 업무 오류를 발생시킬 수 있다 (Chan, 2009;Dorrian et al, 2008).…”
Section: 수면장애는 교대근무를 하는 간호사들에게 흔히 발생하는 문제로 알려져 있다 외국의 경우 교대근무 간호사들의unclassified
“…Sleep is crucial for almost every aspect of human well-being. Various studies have shown the poor quality of sleep among shift workers [3,5,7,8]. Poor sleep among shift working nurses is associated with a lower work performance and a higher risk of medical errors which may jeopardize patient's safety [9].…”
Section: Introductionmentioning
confidence: 99%
“…Poor sleep quality not only cause health problems to the nurse itself, but also the patient's safety, such as in taking action and giving medication (medication error) [3].…”
Section: Discussionmentioning
confidence: 99%